¿Negociación salarial secuencial o simultánea? - Barcena-Ruiz, Juan Carlos; Campo, María Luz (Estudios de Economía, 2016)
This paper analyzes the timing of wage bargaining in an unionized market when workers can be organized in firm level unions or in an industry-level union. In equilibrium, the result obtained depends on who decide the timing of the negotiations: the workers or the firm’s owners.